Correlation between food consumption and nutritional status using MUAC Zscore tape - Pozo Verdesoto , Socrates David (2025)
This study evaluated the relationship between dietary consumption patterns and nutritional ranges determined using the MUAC Z-score tape in Ecuadorian students. A quantitative descriptive analysis was conducted with 128 children aged 3 to 12 years from a rural school in Guayas during the 2025-2026 school year, utilizing a Food Consumption Frequency Questionnaire (CFCA) and anthropometric measurements. The results indicated that 63% of the students had normal nutrition, 23% had mild malnutrition, and 5% had moderate malnutrition. Children with adequate nutrition consumed dairy products, meats, fruits, and vegetables more frequently than those who were malnourished. A significant association was found (p<0.001) between low consumption of nutritious foods and malnutrition, confirming that the MUAC Z-score tape is a useful tool for nutritional assessment in rural contexts.